Optimal Taxation, Marriage, Home Production, and Family Labor Supply - Gayle, George-Levi; Shephard, Andrew (Econometrica, 2019)
An empirical approach to optimal income taxation design is developed within an equilibrium collective marriage market model with imperfectly transferable utility. Taxes distort time allocation decisions, as well as marriage market outcomes, and the within household decision process. Using data from the American Community Survey and American Time Use Survey, we structurally estimate our model and explore empirical design problems. We allow taxes to depend upon marital status, with the form of tax jointness for married couples unrestricted. We find that the optimal tax system for married couples is characterized by negative jointness, although the welfare gains from jointness are modest. These welfare gains are then shown to be increasing in the gender wage gap, with taxes here, as in the case of gender based taxation, providing an instrument to address within household inequality.